The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1464-410x.2012.11450.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer: germline prediction for a commonly variable malignancy

Abstract: What ' s known on the subject? and What does the study add? Prostate cancer is a heterogeneous disease and biomarkers to predict its incidence and subsequent clinical behaviour are needed to tailor screening, prevention and therapeutic strategies. Rare mutations in genes such as BRCA1, BRCA2 and HOXB13 can affect prostate cancer incidence and/or clinical behaviour. Genome wide association studies (GWAS) have identifi ed more common genetic variations that explain an estimated 20% of familial prostate cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…These two tumor suppressor genes are involved in the maintenance of genomic stability through their role in double‐strand DNA repair and mutations in DNA repair genes have been linked to both early‐onset and hereditary prostate cancer, as well as more aggressive clinical features time of diagnosis, with earlier progression to metastatic disease and higher prostate cancer‐specific mortality . Moreover, BRCA1/2 mutations have also been connected to response to therapy in prostate cancer, in particular response to treatment with platinum‐based chemotherapy and Poly (ADP‐ribose) polymerase (PARP) inhibitors . Clinical trial results suggest that BRCA2 mutation carriers with metastatic castrate resistant prostate cancer treated with olaparib experience high response to treatment .…”
Section: Discussionmentioning
confidence: 99%
“…These two tumor suppressor genes are involved in the maintenance of genomic stability through their role in double‐strand DNA repair and mutations in DNA repair genes have been linked to both early‐onset and hereditary prostate cancer, as well as more aggressive clinical features time of diagnosis, with earlier progression to metastatic disease and higher prostate cancer‐specific mortality . Moreover, BRCA1/2 mutations have also been connected to response to therapy in prostate cancer, in particular response to treatment with platinum‐based chemotherapy and Poly (ADP‐ribose) polymerase (PARP) inhibitors . Clinical trial results suggest that BRCA2 mutation carriers with metastatic castrate resistant prostate cancer treated with olaparib experience high response to treatment .…”
Section: Discussionmentioning
confidence: 99%
“…A familial history of prostate cancer, increasing age, ethnicity, low testosterone levels, diet rich in fats, and BRCA1/2 mutations can contribute to the development of this neoplasm [56, 113115]. GWAS studies and large-scale population screening studies revealed several other susceptibility loci, which include genes HPC1 , HPC10 , HPC14 , and TERT [116119].…”
Section: Proteomic Biomarkers In Solid Tumoursmentioning
confidence: 99%
“…In UC, Gallagher et al (2011a) identified four single nucleotide polymorphisms (SNPs) which predicted a likelihood of response to chemotherapy varying from 19 to 84%. A composite germline and somatic genetic signature could prove to be more predictive than either one alone (Bambury and Gallagher, 2012). …”
Section: Efforts To Improve the Efficacy Of Cytotoxic Chemotherapymentioning
confidence: 99%